Near Real-Time Multi-Class Segmentation for Intravascular Optical Coherence Tomography using Knowledge Distillation - Ruben G A van der Waerden; Rick H J A Volleberg; Pierandrea Cancian; Joske L van der Zande; Thijs J Luttikholt; Xiaojin Gu; Leah Heil; Jan-Quinten Mol; Kensuke Nishimiya; Tomasz Roleder; Clara I Sánchez; Bram van Ginneken; et al. (European Heart Journal - Digital Health, 2026)
Abstract Aims Intravascular optical coherence tomography (OCT) enables high-resolution imaging of the coronary vessel wall, but manual image interpretation is time-consuming and existing automated approaches often require high computational resources and exhibit slow inference times, limiting clinical use. We developed OCT-AID-lite, a neural network for near real-time multi-class OCT segmentation leveraging knowledge distillation and semi-supervised learning to accelerate inference while maintaining segmentation accuracy. Methods and results A state-of-the-art model (OCT-AID) guided a compact U-Net–based student model (OCT-AID-lite) through knowledge distillation-based supervision. OCT-AID-lite was trained on 3,466 manually annotated and 137,961 pseudo-labeled frames after automated quality control. On 389 internal test frames, OCT-AID-lite achieved a forward-pass time of 0.10 seconds for a 540-frame pullback, compared with 24.22 seconds for OCT-AID model (p<0.01). Including pre- and post-processing, total processing time was 5.50 seconds for OCT-AID-lite, compared with 30.62 seconds for OCT-AID (p<0.01). For lipid and calcium plaque classification, OCT-AID-lite reached sensitivity/specificity of 98.1%/74.4% and 89.5%/87.5%, respectively. Pixel-wise segmentation performance on true-positive frames was high for guidewire, catheter, lumen, intima, and media (Dice: 0.79–0.99), moderate to high for sidebranch, lipid, and calcium (Dice: 0.76–0.78), and more variable for rare complex classes (Dice: 0.39–0.67). On an independent external test set, model predictions were in agreement with expert assessment. Conclusions OCT-AID-lite enables accurate OCT segmentation in near real-time, allowing efficient quantitative characterization of plaque and vessel structures.